Valuing the Student Voice: Understanding and Responding to Student Concerns - Craig D Hlavac; Sarah E Gossman (Academic Chairpersons Conference Proceedings, 2022)
Many higher education institutions unintentionally make it challenging for students to raise concerns. Students often feel intimidated by faculty and administrators, yet most grievance processes require students to take the initiative to voice a concern. Adding stress is the lack of clarity of these processes, which can make students feel disconnected and uncertain where to turn. To alleviate the stress of students, alternative perspectives must be considered. This session will provide participants with practical strategies for developing processes that respect the student voice and encourage students to bring forward their concerns. Group discussions and scenario-based breakout sessions will be included.
Keywords: student voice; self-advocacy; student/faculty communication; conflict resolution